Mental health status among Malaysian youth - a nationwide cross sectional study - M, Fadzilah; MA, Syifa’; D, Rahima; I Irmi, Zarina; K S, Hayati (Academy of Family Physicians of Malaysia, 2022)
Mental health disorder is one of the global health burdens that seems to be increasing in number. Depression, anxiety, and stress among young adult has increased tremendously, especially during pandemic COVID 19. This nationwide study, aimed to determine the prevalence and factors associated with depression, anxiety, and stress among Malaysia youths.